2009
DOI: 10.1111/j.1476-5381.2008.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 couples through EP4 prostanoid receptors to induce IL‐8 production in human colonic epithelial cell lines

Abstract: Background and purpose: Prostaglandin (PG) E2 and interleukin (IL)-8 are simultaneously increased during the inflammation that characterizes numerous pathologies such as inflammatory bowel disease. IL-8 is a potent neutrophil chemo-attractant and activator, and can initiate and/or exacerbate tissue injury. PGE2 signals principally through prostanoid receptors of the EP2 and/or EP4 subtypes to promote cAMP-dependent cellular functions. The aim of this study was to identify the role of the EP2 and EP4 receptor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 31 publications
6
31
0
Order By: Relevance
“…However, upon induction, its production can increase by more than 100-fold [9] showing highly controlled regulation. We have previously shown that PGE 2 signals through the EP4 receptor to activate cAMP and upregulated IL-8 expression [10], but the mechanistic details are unknown. cAMP can activate the transcription factor CREB to promote binding to cAMP response element (CRE) or similar DNA binding sites in several gene promoters [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, upon induction, its production can increase by more than 100-fold [9] showing highly controlled regulation. We have previously shown that PGE 2 signals through the EP4 receptor to activate cAMP and upregulated IL-8 expression [10], but the mechanistic details are unknown. cAMP can activate the transcription factor CREB to promote binding to cAMP response element (CRE) or similar DNA binding sites in several gene promoters [11].…”
Section: Introductionmentioning
confidence: 99%
“…The two receptors also differ in the rate of desensitization and internalization [23] and affinity to metabolites of the primary ligand PGE 2 . These observations suggest that the subtle differences in EP2 and EP4 receptor expression and signalling may help in fine tuning cellular responses to PGE 2 .In this study, we used colonic epithelial cells which overexpress either the EP2 or EP4 receptor in Caco2 human colonic epithelial cells [10]. PGE 2 was found to drive the activation of CREB and increase IL-8 expression when it preferentially coupled through EP4 receptor.…”
mentioning
confidence: 99%
“…In response to PGN stimulation, PTGER4 could increase cAMP levels and induce IL-6 production in RAW 264.7 macrophages [24]. In colonic inflammation, IL-8, an important mediator of the acute host inflammatory response, was induced by PGE2-PTGER4 signaling via a cAMP-dependent mechanism [25]. Additionally, the activation of PTGER4 may also regulate anti-inflammatory responses in certain cell types by inhibiting stimulus-induced expression of proinflammatory genes, including TNF-a, IFN-b, IL-1b and iNOS [14,17e19].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PTGER4-induced NF-kB activation plays a key role in diverse biological processes, including the pro-inflammatory and pro-survival responses [25,41]. For example, the activation of the NF-kB signaling pathway mediated by PGERT4, as well as PTGER2, could induce IL-6 production in PGN-treated RAW 264.7 macrophages [25]. Additionally, PGERT4 was also shown to promote survival pathways and impair intrinsic apoptotic pathways by activating the NF-kB signaling pathway in human endometriotic cells [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation